Pengembangan Media Pembelajaran E-Modul Pekerjaan Dasar Teknik Mesin untuk siswa SMK - Ahmadi, Maftakhur Rizqi; Sitompul, Nurmida Catherine; Hartono, Hartono (IKIP PGRI Bojonegoro, 2022)
Abstract: Development of teaching materials is a process to produce innovation in teaching and learning activities. The research aims to produce learning products in the form of electronic modules in the subject of Basic Mechanical Engineering Work. Develop learning media in the form of e-modules whose contents are not just basic concepts of mechanical engineering vocational competence, but images, sounds, animations and videos will also be displayed so that students can more easily understand the material being taught and can increase students' attention to the material. being taught. The research subjects were students of class X Welding Engineering Department at SMK Negeri 2 Lamongan. Product development of teaching materials for basic work Mechanical engineering is a research and development (R & D) model of Dick & Carey. The results of the research are learning products in the form of e-modules that have gone through a feasibility test involving reviews of experts, namely material experts, learning design experts and media experts as well as feasibility tests through peer trials, small groups and field tests. The formative evaluation shows that this product is classified as